2013
DOI: 10.26719/2013.19.1.88
|View full text |Cite
|
Sign up to set email alerts
|

Salmonella spp. in patients suffering from enteric fever and food poisoning in Thamar city, Yemen

Abstract: Salmonella remains a public health concern around the world, including Yemen although data on its incidence are few. This study determined the incidence of Salmonella infection in 250 enteric fever and 210 food poisoning cases attending Thamar general hospital and Dar Alshafaa medical clinic in 2008. In total, 773 clinical specimens were taken: 250 blood, 187 urine and 336 stool samples. Of the patients with enteric fever and food poisoning, 16.4% and 15.2% respectively were infected with Salmonella. The serov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
(16 reference statements)
0
8
0
Order By: Relevance
“…The second highest pooled Salmonella prevalence was in GIT symptomatic patients (7.1%, 95% CI: 5.4%–9.1%). Two of the 61 study measures were among GIT symptomatic patients with suspected foodborne illness in Saudi Arabia in 2010 (64.5%, 95% CI: 52.1%–75.3%) (Aljoudi et al, ) and in Yemen in 2013 (15.2%, 95% CI: 11.0%–20.7%) (Taha et al, ). The pooled Salmonella prevalence was 2.2‐time higher in GIT symptomatic patients tested before year 2000 than patients tested after year 2000 (13.0% vs. 6.0%).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The second highest pooled Salmonella prevalence was in GIT symptomatic patients (7.1%, 95% CI: 5.4%–9.1%). Two of the 61 study measures were among GIT symptomatic patients with suspected foodborne illness in Saudi Arabia in 2010 (64.5%, 95% CI: 52.1%–75.3%) (Aljoudi et al, ) and in Yemen in 2013 (15.2%, 95% CI: 11.0%–20.7%) (Taha et al, ). The pooled Salmonella prevalence was 2.2‐time higher in GIT symptomatic patients tested before year 2000 than patients tested after year 2000 (13.0% vs. 6.0%).…”
Section: Resultsmentioning
confidence: 99%
“…These research reports were conducted in 15 countries (Bahrain, Iraq, Jordan, Kuwait, Lebanon, Libya, Morocco, Oman, Palestine, Qatar, Saudi Arabia, Sudan, Tunisia, United Arab Emirates and Yemen) out of the 23 countries of MENA region. Of the 46 reports, 26.1% were in Saudi Arabia (Akhter, Burdette, Burdette, Qadri, & Myint, ; al‐Ahmadi, el Bushra, & al‐Zahrani, ; Albreiki, Al‐Ali, Al‐Ali, & Rayan, ; al‐Freihi et al, ; Al‐Ghamdi, ; Aljoudi, Al‐Mazam, Al‐Mazam, & Choudhry, ; Asghar, Zafar, Zafar, & Momenah, ; Elhadi, Aljindan, Aljindan, & Aljeldah, ; el‐Sheikh & el‐Assouli, ; Johargy, Ghazi, Ghazi, & Mumenah, ; Ramadan, Unni, Unni, Hablas, & Rizk, ; Zaman, ), 13.0% in Tunisia (Abbassi‐Ghozzi et al, ; Al‐Gallas, Bahri, Bahri, Bouratbeen, Ben Haasen, & Ben Aissa, ; Ben Aissa, Al‐Gallas, Al‐Gallas, Troudi, Belhadj, & Belhadj, ; Ben Salem‐Ben Nejma et al, ; Bouallegue‐Godet et al, ; Hammami et al, ), 10.9% in Jordan (Abdel‐Dayem, Al Zou'bi, Al Zou'bi, Hani, & Amr, ; Gargouri et al, ; Nimri & Meqdam, ; Shehabi, Abu‐Ragheb, Abu‐Ragheb, & Allaham, ; Youssef et al, ), 6.5% in Morocco (Aiat Melloul & Hassani, ; Ammari et al, ; Benmessaoud et al, ), 6.5% in Qatar (Al‐Thani, Baris, Baris, Al‐Lawati, & Al‐Dhahry, ; Ghunaim et al, ; Weam et al, ), 6.5% in Palestine (Abu Elamreen, Abed, Abed, & Sharif, ; Abu Elamreen, Sharif, Sharif, & Deeb, ; Laham, Elyazji, Elyazji, Al‐Haddad, & Ridwan, ) and 4.3% in each of Iraq (Al‐Kubaisy et al, ; Alrifai, Alsaadi, Alsaadi, Mahmood, Ali, & Al‐Kaisi, ), Libya (Ali, Ghenghesh, Ghenghesh, Aissa, Abuhelfaia, & Dufani, ; Rahouma et al, ), Oman (Al‐Bahry, Elshafie, Elshafie, Al‐Busaidy, Al‐Hinai, & Al‐Shidi, ; Patel, Mercy, Mercy, Shenoy, & Ashwini, ), Sudan (El Hussein et al, ; Elhag, Saeed, Saeed, Omer, & Path, ) and Yemen (Banajeh, Ba‐Oum, Ba‐Oum, & Al‐Sanabani, ; Taha, Alghalibi, Alghalibi, & Saeedsaleh, ). Only one research report was found in each of Bahrain (Ismaeel, Jamsheer, Jamsheer, Yousif, Al‐Otaibi, & Botta, ), Kuwait (Jamal, Pauline, Pauli...…”
Section: Resultsmentioning
confidence: 99%
“…Staphylococcus aureus, Shigella sp., Escherichia coli, Salmonella sp. and Clostridium perfringens are common pathogens that may exist on the skin as transient flora and can cause infectious diarrhea [36][37][38] .…”
Section: Discussionmentioning
confidence: 99%
“…Several published studies (Table 2) indicate that the most widely reported serovars associated with acute diarrhoeal disease across the EMR are the Salmonella serovar Typhimurium and Salmonella serovar Enteritidis [73,76,80]. Similar to the situation in EMR, S. Typhimurium followed by S .…”
Section: Implication Of Nts In Diarrhoeal Illnesses In the Emrmentioning
confidence: 98%
“…Published studies reporting the rates of NTS in the EMR countries are summarised in Table 2. Studies from Iraq (Mosul) [68], Iran (Tehran) [72], Saudi Arabia [27], Kuwait [31], Morocco (Marrakesh) [43] and Yemen [73] reveal a noteworthy high incidence rate (15% to 34%) of NTS (Table 2).…”
Section: Implication Of Nts In Diarrhoeal Illnesses In the Emrmentioning
confidence: 99%